2014
DOI: 10.1007/s13277-014-2690-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of chitinase 3-like 1 is a prognosis marker for non-small cell lung cancer correlated with tumor angiogenesis

Abstract: Increasing evidence demonstrated that chitinase 3-like 1 (CHI3L1) was highly expressed and tightly associated with human tumor development and progression. However, its precise role in non-small cell lung cancer (NSCLC) remains to be delineated. The aim of this study was to examine CHI3L1 expression in patients with NSCLC and explore the relationship of CHI3L1 protein with clinicopathologic factors, tumor angiogenesis, and prognosis. CHI3L1 protein and intratumoral microvessels were examined by immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In addition, the MVD in HCC tissues was significantly higher compared with tumor-adjacent and normal liver tissues. These results suggest that Ang-1 is important for microvessel formation in HCC, which is consistent with the results of previous studies (18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the MVD in HCC tissues was significantly higher compared with tumor-adjacent and normal liver tissues. These results suggest that Ang-1 is important for microvessel formation in HCC, which is consistent with the results of previous studies (18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 93%
“…The MVD (CD34) in HCC, tumor-adjacent and normal liver tissues was determined using IHC analysis of CD34 as previously described (18)(19)(20)(21). CD34-positive cells were predominantly detected in the cancer cell nest and hepatic blood sinus (Fig.…”
Section: Mvd In Hcc Tumor-adjacent and Normal Liver Tissuesmentioning
confidence: 99%
“…In the 3 articles about urogenital system cancer using OS to assess clinical outcome, the combined HR 1.31 (95% CI: 0.91-1.87, P = 0.144), implying the association between overexpression of YKL-40 and poor OS was not signi cant ( Figures S1). Interestingly, the heterogeneity showed a remarkable change in the research region Ykl-40 And Dfs DFS data were reported or extrapolated from 11 studies, representing a total of 2092 patients (26,27,29,32,37,41,43,(45)(46)(47)(48)(49). The pooled HR and 95%CI was calculated by using a xed-effects model, heterogeneities between HR estimates was no signi cantly in this meta-analysis (I 2 = 18.6; P = 0.267).…”
Section: Characteristics and Quality Assessment Of The Included Studiesmentioning
confidence: 80%
“…YKL-40, additionally termed CHI3L1, is produced by a variety of cells (10), including macrophages, neutrophils, eosinophils, vascular smooth muscle cells, endothelial cells and cancer cells. Elevated levels of serum YKL-40 protein have been reported in a number of other types of cancer, including glioma (11) cholangiocarcinoma (12), colorectal cancer (13), non-small cell lung cancer (14), renal cell cancer (15) and osteosarcoma (16). YKL-40 may also be expressed within local inflammatory cells in inflamed tissues (17,18) and it is considered to be a biomarker in inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%